Redefining hacking a comprehensive guide to red teaming and bug bounty hunting in an AI-driven world - Santos, Omar; Lazzara, Savannah; Thurner, Wesley (Addison-Wesley, 2025)
Redefining Hacking: A Comprehensive Guide to Red Teaming and Bug Bounty Hunting in an AI-Driven World equips cybersecurity professionals, students, and tech enthusiasts with modern hacking methodologies and the tools to combat evolving threats. Written by industry experts Omar Santos, Savannah Lazzara, and Wesley Thurner, this book blends real-world insights with forward-looking perspectives on AI, automation, and quantum computing. Packed with hands-on exercises, actionable strategies, and case studies, it empowers readers to think like attackers while proactively strengthening their defenses. Gain practical knowledge to master red teaming, bug bounty hunting, and prepare for an AI-influenced cybersecurity landscape.
Includes bibliographical references and index
Keywords: Penetration testing (Computer security); Artificial intelligence; Computer networks -- Security measures; Hacking; Computer security; Tests d'intrusion; Intelligence artificielle; Réseaux d'ordinateurs; Sécurité; Mesures; Piratage informatique; Sécurité informatique; artificial intelligence